Encyclopedia of modern Asia - Levinson, David; Christensen, Karen (Charles Scribner's Sons, 2002)
A six-volume survey of modern Asia, defined as extending from Japan in the east to Turkey in the west, and from Kazakhstan in the north to Indonesia in the south. Presents entries covering such subjects as countries, cities, regions, natural features, religions, social issues, languages, people, events, customs, politics, and economics
Includes bibliographical references
Keywords: Asia -- Encyclopedias; Asia -- Economic conditions; Asia -- Politics and government; Asia -- Social conditions; Wörterbuch; Asien